MON-161 Lipolytic Rate in Relation to Skeletal Muscle and Hepatic Insulin Resistance - Levine, Jordan (J Endocr Soc, 2019)
Introduction: Increased circulating free fatty acid (FFA) due to impaired control of adipocyte triglyceride lipolysis contributes to the development of obesity-related insulin resistance (IR). However, it is less clear whether there are differences in the relationship between lipolysis and skeletal muscle vs hepatic IR, or how these relationships are influenced by age, race, sex, body composition, or inflammation. We investigated the associations of lipolytic rate (LR) with skeletal muscle insulin sensitivity, as evidenced by insulin sensitivity index (SI), and hepatic IR, as measured by HOMA-IR. Methods: 46 healthy, non-diabetic adults with obesity (BMI 39.8±6.9 kg/m(2)) and 11 lean (BMI 25.6±2.1 kg/m(2)) adults (40% NHB, 20% HISP, 37% NHW, 3% Asian; 65% female; age 45.8±12.6y) underwent fasting blood draws and an insulin-modified frequently sampled intravenous glucose tolerance test (FSIVGTT). LR was calculated by a mathematical minimal model that estimated basal lipolysis and insulin-mediated lipolysis stimulated by insulin modulation of FFA during the FSIVGTT; SI was derived from Bergman’s minimal model. Body composition was determined by DXA. Using ANCOVA, we examined how LR was related to SI and HOMA-IR, controlling for age, race, and sex. Secondary analyses examined if the differences seen could be accounted for by differences in total fat mass or hsCRP. Results: As expected, LR was significantly elevated in adults with obesity (Mean±SD: 0.069±0.047 vs. 0.0052±0.00084 mEq/L*min, p<.001) and was positively correlated with total fat mass (r= +.64, p<.001). LR was also correlated with fasting insulin (r=.+56, p<.001), HOMA-IR (r= +.57, p<.001), SI (r= -.39, p<.01), and hsCRP (r= +.70, p<.001). Controlling for age, race, and sex (all ps>.05), LR remained correlated with SI (B= -.24, p<.01) and with HOMA-IR (B= +.33, p<.001). However, for SI, after including total fat mass and hsCRP in the model, the effect of LR on SI was no longer observed (p>.05). By contrast, for HOMA-IR, even after including total fat mass and hsCRP in the model, the effect of LR was still observed (B= +.30, p<.05). Conclusions: Previous studies have shown that excessive lipolysis plays a significant role in the pathogenesis of IR. By minimal model analysis of an insulin-modified FSIVGTT, we confirmed the well-described association of increased LR with skeletal muscle and hepatic IR. We found that differences in total fat mass fully explained the LR effect in skeletal muscle IR. However, even after controlling for total fat mass and hsCRP, our model revealed a significant association of LR with HOMA-IR. Our data suggest that LR is likely a strong predictor of hepatic IR across age, race, and sex in human obesity. Further studies are warranted to investigate how adiposity and inflammation mediate this relationship between lipolysis and IR.